Citizen-Centric Governance and Public Service Transformation in the Digital Era: A Case of Banyuwangi, Indonesia - Anggun Artisa, Rike; Yecyec, Faye Lorraine M.; Fadhlurrohman, Mochammad Iqbal (Jurnal Studi Pemerintahan, 2026)
ABSTRACT This study examines the implementation of citizen-centric governance within local digital transformation by analyzing the Electronic-Based Government System (EBGS), nationally known as Sistem Pemerintahan Berbasis Elektronik (SPBE), in Banyuwangi Regency, Indonesia. While previous studies on digital government have largely focused on technical readiness, system integration, and performance indices, this research emphasizes the importance of citizen experience, participation, and public value creation. Adopting a qualitative case study approach, the study explores how citizen-centric principles are institutionalized in digital public service delivery. Data were collected through in-depth semi-structured interviews with key government officials and citizens, non-participant observation of digital service practices, and analysis of policy documents, official reports, and digital governance evaluations. The findings reveal that Banyuwangi’s digital transformation is supported by strong data transparency, hybrid participation mechanisms combining digital and non-digital channels, responsive public service delivery, and collaborative co-production between government and citizens. These practices foster interactive governance characterized by two-way communication, adaptive service design, and contextual responsiveness to citizens’ capacities and needs. The interaction between transparency, participation, and responsiveness generates value co-creation in the form of individual benefits, social cohesion, and increased political legitimacy. This study demonstrates that successful local digital transformation is not solely determined by technological sophistication or administrative performance, but by the extent to which digital governance embeds citizen-centric values into institutional practices. The research contributes to digital governance literature by empirically integrating citizen-centric governance, co-production, and public value perspectives within a developing country context. ABSTRAK Studi ini meneliti implementasi tata kelola yang berpusat pada warga dalam transformasi digital lokal dengan menganalisis Sistem Pemerintahan Berbasis Elektronik (SPBE) di Kabupaten Banyuwangi, Indonesia. Sementara studi-studi sebelumnya tentang pemerintahan digital sebagian besar berfokus pada kesiapan teknis, integrasi sistem, dan indeks kinerja, penelitian ini menekankan pentingnya pengalaman warga, partisipasi, dan penciptaan nilai publik. Dengan mengadopsi pendekatan studi kasus kualitatif, studi ini mengeksplorasi bagaimana prinsip-prinsip yang berpusat pada warga diinstitusionalisasikan dalam penyampaian layanan publik digital. Data dikumpulkan melalui wawancara semi-terstruktur mendalam dengan pejabat pemerintah dan warga kunci, observasi non-partisipan terhadap praktik layanan digital, dan analisis dokumen kebijakan, laporan resmi, dan evaluasi tata kelola digital. Temuan menunjukkan bahwa transformasi digital Banyuwangi didukung oleh transparansi data yang kuat, mekanisme partisipasi hibrida yang menggabungkan saluran digital dan non-digital, penyampaian layanan publik yang responsif, dan produksi bersama yang kolaboratif antara pemerintah dan warga. Praktik-praktik ini mendorong tata kelola interaktif yang dicirikan oleh komunikasi dua arah, desain layanan adaptif, dan responsivitas kontekstual terhadap kapasitas dan kebutuhan warga. Interaksi antara transparansi, partisipasi, dan daya tanggap menghasilkan penciptaan nilai bersama dalam bentuk manfaat individu, kohesi sosial, dan peningkatan legitimasi politik. Studi ini menunjukkan bahwa transformasi digital lokal yang sukses tidak hanya ditentukan oleh kecanggihan teknologi atau kinerja administratif, tetapi juga oleh sejauh mana tata kelola digital menanamkan nilai-nilai yang berpusat pada warga negara ke dalam praktik kelembagaan. Penelitian ini berkontribusi pada literatur tata kelola digital dengan secara empiris mengintegrasikan tata kelola yang berpusat pada warga negara, produksi bersama, dan perspektif nilai publik dalam konteks negara berkembang.